Paleointensity during a chron C26r excursion recorded in west Greenland lava flows (Dataset) ... - Riisager, Janna; Riisager, Peter; Xixi Zhao; Coe, Robert S.; Pedersen, Asger Ken (Magnetics Information Consortium (MagIC), 2010)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Paleointensity during a chron C26r excursion recorded in west Greenland lava flows ...